2022
DOI: 10.1111/1541-4337.12945
|View full text |Cite
|
Sign up to set email alerts
|

Adzuki bean (Vigna angularis): Chemical compositions, physicochemical properties, health benefits, and food applications

Abstract: Adzuki bean (Vigna angularis), also called red bean, is a legume of Fabaceae (Leguminosae) family. This crop is native to East Asia and is also commercially available in other parts of the world. It is becoming a research focus owing to its distinct nutritional properties (e.g., abundant in polyphenols). The diverse health benefits and multiple utilization of this pulse are associated with its unique composition. However, there is a paucity of reviews focusing on the nutritional properties and potent applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 144 publications
(353 reference statements)
0
11
0
Order By: Relevance
“…For example, it can prevent hypertension, diabetes, and heart disease. In addition, it also has certain effects in antioxidant, immune regulation, gastrointestinal protection, anti-tumor, and antibacterial ( 2 , 3 ). A large number of experiments have shown that polysaccharides are important biologically active components in legumes, and the biological activity is closely related to the structure of polysaccharides ( 43 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it can prevent hypertension, diabetes, and heart disease. In addition, it also has certain effects in antioxidant, immune regulation, gastrointestinal protection, anti-tumor, and antibacterial ( 2 , 3 ). A large number of experiments have shown that polysaccharides are important biologically active components in legumes, and the biological activity is closely related to the structure of polysaccharides ( 43 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Legumes mainly include soybeans, black beans, adzuki beans, mung beans, lentils, cowpeas, kidney beans, peas, chickpeas, etc. Modern chemical and pharmacological studies have shown a positive correlation between the consumption of legumes and a reduced risk of Chronic metabolic diseases, such as cardiovascular disease, diabetes, obesity and cancer ( 1 , 2 ). This is related to the fact that legumes are rich in polysaccharides, protein, vitamins, minerals, unsaturated fatty acids, phenolic compounds and other beneficial nutritional factors ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phaseolus angularis seeds have various effects, such as alleviating edema, eliminating inflammation, and relieving poisoning effects [ 10 ]. Moreover, they are rich in vitamin B1, which helps to recover from fatigue and is effective against symptoms, such as digestion difficulties, absorption impairment, and memory loss [ 11 ]. P. angularis has been reported to exert antidiabetic, antioxidant, and anti-inflammatory effects [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adzuki beans ( Vigna angularis ) are common legumes appearing in red, white, black, and green colors ( 1 , 2 ). China is the largest cultivator and distributes these beans to Japan, Korea, the Philippines, and Malaysia ( 3 ).…”
Section: Introductionmentioning
confidence: 99%